2020
DOI: 10.1016/j.arth.2020.01.031
|View full text |Cite
|
Sign up to set email alerts
|

The Majority of Total Hip Arthroplasty Patients With a Stiff Spine Do Not Have an Instrumented Fusion

Abstract: Background: Total hip arthroplasty (THA) patients with limited lumbar flexion (LF) have increased rates of dislocation. An instrumented spinal fusion is a well-recognized cause whose risk increases with increasing number of levels fused. However, many patients without an instrumented fusion (IF) also exhibit abnormal spinopelvic mobility. The purpose of this study was to understand the proportion of THA patients without an IF that have a stiff spine (SS) and behave as if they are surgically fused. Methods: A r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 20 publications
0
24
0
2
Order By: Relevance
“…Alternatively, lumbar spine stiffness resulting from degenerative disc disease, lumbar flatback deformity, or lumbar fusion decreases overall motion, and is present in around 6% of THA patients. 15,16 During relaxed sitting, a stiff lumbar spine does not straighten its lordosis and the pelvis does not tilt posteriorly. Further, some patients with stiff lumbar spines have even demonstrated more anterior pelvic tilting with flexed sitting (i.e.…”
Section: Pelvic Considerationsmentioning
confidence: 99%
“…Alternatively, lumbar spine stiffness resulting from degenerative disc disease, lumbar flatback deformity, or lumbar fusion decreases overall motion, and is present in around 6% of THA patients. 15,16 During relaxed sitting, a stiff lumbar spine does not straighten its lordosis and the pelvis does not tilt posteriorly. Further, some patients with stiff lumbar spines have even demonstrated more anterior pelvic tilting with flexed sitting (i.e.…”
Section: Pelvic Considerationsmentioning
confidence: 99%
“…Abnormal spinopelvic mobility is increasingly being recognized as a contributing factor to postoperative complications such as impingement and dislocation after total hip arthroplasty (THA). Recent studies have demonstrated the significance of the hip-spine relationship and how it affects the dynamic spine-pelvic-hip kinetic chain during movement [ [1] , [2] , [3] , [4] , [5] , [6] , [7] ]. Pathologic alterations to this coordinated motion as a result of spinopelvic stiffness have implications on functional acetabular cup positioning [ [8] , [9] , [10] , [11] ].…”
Section: Introductionmentioning
confidence: 99%
“…Assessing pelvic tilt changes with static based radiographs is important for determining optimized acetabular component positioning and orientation [ [15] , [16] , [17] , [18] ]. Posterior pelvic tilt with standing as occuring with sagittal spinal imbalance, for instance, increases functional inclination and anteversion of a cup relative to the supine position, and a posterior rotation that is large enough would take a well-positioned cup out of the LSZ [ [1] , [2] , [3] , [4] , 19 ]. Conversely, an anterior pelvic tilt when standing will decrease functional inclination and anteversion of a cup relative to supine [ [1] , [2] , [3] , [4] , 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SPT changes with spinal pathologies as well as spinal surgeries, but there is limited evidence regarding the magnitude of SPT change that can increase the risk for postoperative THA dislocation. The criteria that is known is the spinal stiffness (SPT change less than 10°) that can increase the risk of dislocation 17‐19 . The risk has been assessed by lateral lumbosacral radiographs in standing and sitting positions or advanced functional imaging techniques, such as bi‐planer radiography (EOS; EOS imaging).…”
Section: Introductionmentioning
confidence: 99%